1998
DOI: 10.1002/yd.23319988007
|View full text |Cite
|
Sign up to set email alerts
|

Religious‐issues group therapy

Abstract: The long‐standing success of a Spiritual Beliefs and Values Group supports the potential value of discussing spiritual issues and challenges the assumption that religious concerns voiced by people with serious mental illness should be considered pathological.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Over half reported that their church community played a positive role in their coping. Efforts to find ways to build collaboration with faith communities in providing recovery support and ongoing fellowship (Kehoe, 1998) should be maintained and increased. Most importantly, our participants continued to remind us, as we found so clearly in our initial work, the critical importance of being part of a caring community.…”
Section: Discussionmentioning
confidence: 99%
“…Over half reported that their church community played a positive role in their coping. Efforts to find ways to build collaboration with faith communities in providing recovery support and ongoing fellowship (Kehoe, 1998) should be maintained and increased. Most importantly, our participants continued to remind us, as we found so clearly in our initial work, the critical importance of being part of a caring community.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these controlled clinical trials, the use of religiously-and spirituallyintegrated group treatments have also been examined using non-controlled designs. Several spiritually-integrated group treatment protocols have been created for individuals with severe mental illness (e.g., Kehoe, 1998;Lingdren & Coursey, 1995;O'Rourke, 1997;Phillips et al, 2002;Sageman, 2004). Using a pre-test post-test design, Lindgren and Coursey (1995) found that participants in the treatment program increased in perceived spiritual support following treatment.…”
Section: Journal Of Psychology and Theology Counseling And Values) mentioning
confidence: 99%
“…Since then, numerous descriptive articles and a small number of empirical articles have focused almost exclusively on psychoeducational groups (Avants, Beitel, Margolin, 2005;Lindgren & Coursey, 1995;Phillips, Lakin, & Pargament, 2002;McCorkle, 2005;Revheim, Greenberg, & Citrome, 2010;Richards, Owen, Stein, 1993;Rye & Pargament, 2002;Tarakeshwar, Pearce, Sikkema, 2005;Worthington, 2004). A search of the literature located seven articles that described psychotherapy groups that specifically addressed religious and spiritual concerns (Cole & Pargament, 1998;Genia, 1990;Kehoe, 1998;O'Rourke, 1997;Richards, Berrett, Hardman, & Eggett, 2006;Zinnbauer & Camerota, 2004).…”
Section: Group Counseling and Religion And Spiritualitymentioning
confidence: 99%
“…Most attempts to incorporate discussion of religious and spiritual issues into counseling groups have occurred within the contexts of treatment centers for the mentally ill (Kehoe, 1998;Lindgren & Coursey, 1995;O'Rourke, 1997;Phillips et al, 2002;Revheim et al, 2010). Other articles provided descriptions of psychoeducational groups designed for homogenous populations, such as adults coping with addiction, HIV, cancer, disordered eating, social anxiety, and romantic partner betrayal (Avants et al, 2005;McCorkle et al, 2005;Richards et al, 2006, Rye & Pargament, 2002, Rye et al, 2005Tarakeshwar et al, 2005).…”
Section: Group Formats For Addressing Religious and Spiritual Concernsmentioning
confidence: 99%
See 1 more Smart Citation